2010
DOI: 10.1007/s11033-010-0562-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HBV genotypes among Egyptian hepatitis patients

Abstract: Phylogenetic analysis has led to the classification of hepatitis B virus into eight genotypes, designated A to H. The genotypes have differences in biological properties and show heterogeneity in their global distribution. These attributes of the genotypes may account not only for differences in the prevalence of hepatitis B virus mutants in various geographic regions, but also makes them responsible for differences in the clinical outcome and response to antiviral treatment in different population groups. Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 42 publications
5
24
1
Order By: Relevance
“…Predominantly patients in the non-replicative phase are characterized by seroconversion of HBeAg to anti-HBe, very low or undetectable serum HBV DNA levels (usually <2000 IU/ ml) and normal serum aminotransferases (approximately 40 IU/ml) conferring a favorable long-term outcome due to immunological control of the infection [3,25,26]. Similar results were obtained by Khaled et al [19] who found from 140 HBV infected patients (all of them were positive for HBsAg) only 100 patients were positive for HBV DNA.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Predominantly patients in the non-replicative phase are characterized by seroconversion of HBeAg to anti-HBe, very low or undetectable serum HBV DNA levels (usually <2000 IU/ ml) and normal serum aminotransferases (approximately 40 IU/ml) conferring a favorable long-term outcome due to immunological control of the infection [3,25,26]. Similar results were obtained by Khaled et al [19] who found from 140 HBV infected patients (all of them were positive for HBsAg) only 100 patients were positive for HBV DNA.…”
Section: Discussionmentioning
confidence: 76%
“…Also, Al-Aboudi and Al-Hmudi [18] reported that 28.5% of patients were positive for HBsAg whereas 24.2% of recovery patients were positive for this antigen. In Egypt, Khaled et al [19] studied 140 HBV Egyptian patients and found that all of them were positive for HBsAg. In Iran, Ghafourian et al [20] showed that among 58 of CHB patients 55 (94.8%) were positive for HBsAg.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other studies performed in Egypt have demonstrated the simultaneous presence of HBV genotypes B and D among pediatric patients with cancer [22] and also B and D, with a few A and C, genotypes among hepatocellular carcinoma adult patients in Cairo [23]. Another study reported that HBV genotype D represented 87% of 100 HBV-DNA-positive patients, including 20 patients with acute hepatitis, 75 patients with chronic active hepatitis and 5 patients with hepatocellular carcinoma; the rest of the subjects (all were acute hepatitis cases) had a mixed D/F genotype [24]. …”
Section: Introductionmentioning
confidence: 99%
“…These infections lead to a particularly high morbidity and mortality. (1,2) Blood born diseases (including HBV and HCV infections) are generally more frequent in prisons than in the community. (3,4) These high prevalence can be mostly attributed to conditions often experienced by prisoners before incarceration such as: unsafe lifestyles, psychiatric and social problems.…”
Section: Egypt Many Egyptian Studies Proved That Hbv Infection Is Ofmentioning
confidence: 99%